The mobilities of care in later life: exploring the relationship between caring and mobility in the lives of older people. Issue 8 (11th August 2021) - Croucher, Karen; Gilroy, Rose; Bevan, Mark; Attuyer, Katia
Abstract: There has been a renewed call for a revaluing of informal caring in order to counter the way that caring is undervalued, taken for granted and invisible. Travel is one area where a detailed critique of this issue has emerged with the concept of 'mobility of care', however, this concept has only been applied in relation to younger age groups, and our understanding of mobilities of care in later life remains underdeveloped. By 'mobilities of care' we mean journeys made for the purpose of giving and receiving informal care and support. This paper draws on the mobility narratives of 99 older people (aged 55 and above) living in three locations in the North of England who participated in a two-year qualitative longitudinal study that explored the inter-play between mobility, wellbeing and life transitions. We focused on the experience of managing life transitions rather than assume that chronology per se determines wellbeing. Narratives of ageing emphasise the importance of getting out and about, and being socially connected active citizens. Our study demonstrates that for many older people getting out and about is not for leisure or utility purposes but to give support and care. As such, these journeys have a particular significance in the lives of older people and in the construction of roles, meaning and identity in later life.